The problem of environmental safety of the fields of mining industrial production of arid zone of Kazakhstan - Bexeitova, Roza; Veselova, Larisa; Kassymkanova, Khaini-Kamal; Jangulova, Gulnar; Baidauletova, Gulbanu; Zhalgasbekov, Yermek; Burlibayeva, Shugyla; Turekhanova, Venera (Geodesy and Cartography, 2018)
The urgency of the safety of the components of the natural environment of Central Kazakhstan is due, firstly, to the long development of solid minerals and, in connection with this, the huge expenditure of energy and water resources, and secondly, to the use of obsolete mining technologies. The complex of works on the extraction of solid minerals leads to a change in the entire range of environmental conditions in the mining areas and adjacent areas, which is due to the interconnectedness of all natural components among themselves. The article deals with the processes, associated with work in the mining industry, the beginning of which was laid in the first half of the ХХ century. A prolonged mechanical intervention in the surface, subsurface structures of the earth‘s crust led to the development of a number of dangerous geodynamic processes, that directly and indirectly degrade the ecological state of the surrounding area.